Inovasi Pupuk Organik untuk Pertanian Ramah Lingkungan - Gulo, Aguswita; Lawolo, Asdian Julianti; Zebua, Oscar Zemen; Laoli, Desepi Aferianus; Lase, Natalia Kristiani (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Environmentally friendly agriculture is a sustainable approach to reducing negative impacts on ecosystems. The use of organic fertilizers is a key solution to achieving this goal. Organic fertilizers not only enhance soil fertility naturally but also help reduce the use of synthetic chemicals that can harm the environment. This study aims to examine innovations in the production and use of organic fertilizers to improve efficiency and support sustainable agriculture. The findings indicate that modern technologies, such as microbial bioactivators and biochar, can enhance the quality of organic fertilizers, positively impacting plant productivity and environmental conservation. With proper innovations, organic fertilizers can become an optimal solution for future sustainable agriculture.